Mathematical modeling with multidisciplinary applications - Yang, Xin-She (Hoboken, New Jersey : Wiley, 2013)
"This book details the interdisciplinary nature of mathematical modeling and numerical algorithms. It combines a variety of applications from diverse fields to illustrate how the methods can be used to model physical processes, design new products, find solutions to challenging problems, and increase competitiveness in international markets. Including case studies, worked examples, and exercises, it cover topics such as partial differential equations, fractional calculus, inverse problems by ODEs, semigroups, decision theory, risk analysis, Bayesian estimation, nonlinear PDEs in financial engineering, perturbation analysis, dynamic system modeling, and much more"--
Part I. Introduction and Foundations. Differential Equations / Xin-She Yang ; Mathematical Modelling / Xin-She Yang ; Numerical Methods: An Introduction / Xin-She Yang ; Teaching Mathematical Modelling / Thomas Lingefjärd. -- Part II. Mathematical Modelling with Multidisciplinary Applications. Industrial Mathematics with Applications / Alfredo Bermúdez and Luz M. García García ; Data Analysis in Economics / Ivan Jeliazkov and Mohammad Arshad Rahman ; Inverse Problems in ODEs / H. Kunze and D. La Torre ; Estimation of Model Parameters / Robert Piché ; Parabolic PDE in Financial Engineering / L.A. Boukas, K.I. Vasileiadis, S.Z. Xanthopoulos, A.N. Yannacopoulos ; Decision Modeling in Supply Chain Management / Huajun Tang ; Modelling Pricing Weather Derivatives / Fred Espen Benth ; Decision Theory in Social Sciences / E.V. Petracou and A.N. Yannacopoulos ; Fractals, with applications to signal and image modeling / H. Kunze and D. La Torre ; Efficient Numerical Methods for Singularly Perturbed Differential Equations / S. Natesan. -- Part III. Advanced Modelling Topics. Fractional Calculus and its Applications / Ivo Petráš ; Goal Programming Model / Belaid Aouni, Cinzia Colapinto and Davide La Torre ; Decision Theory and Game Theory / E.V. Petracou and A.N. Yannacopoulos ; Control Problems on Differential Equations / Chuang Zheng ; Markoc-jump stochastic models / Boualem Khouider ; Problem Solutions.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Differential equations; Mathematical models; Differential equations; Mathematical models; MATHEMATICS -- General; Differential equations; Mathematical models; Differential equations; Mathematical models; Electronic books